(عصرِ حاضر میں مسلمانوں کی سیاسی ابتری اور اس کا تدارک (سیرتِ طیبہﷺ کی روشنی میں: Muslims Political deterioration in the modern era and its remedy (In the light of Seerah) - Bakht Shaid; Mufti Syed Muhammad Atiq (Rahat-ul-Quloob, 2018)
The noble life Of Rasulullah (ﷺ) provides the best after course and framework for the individual and collective life of Muslims which can lead Muslims to prosper in each part of life. Out of different problems of the Muslim Ummah in the current circumstances is the absence of political insight and exemplary leadership which is one of the most important problems and due to which Muslims are victim of decline on international basis. The political and national problems of Muslims include the absence of exemplary leadership, Muslim Ummah getting victim of mutual differences, deprivation of the majority of Muslim rulers of bravery and boldness, shortage of the wellbeing of the public, excess of corruption and fraud, absence of self-accountability in the public and rulers, not complying with the rules of justice, shortage of qualified and experienced individuals in different departments and institutions along with some other similar problems. Without getting them solved, the dreams of prosperity and success of Muslim Ummah cannot be fulfilled. We can find the solution of all of these problems in the teachings of Rasulullah (S.A.W) and in his noble life. Hence it is very important to prepare a framework in the light of Seerah and adopt it accordingly in this very important part of life. In the article under reference, Muslims Political deterioration in the modern era and a review of its remedy is to be presented in the light of Seerah.